The Analysis of Students’ Self-Confidence in Speaking Through English Speech Training at Pondok Pesantren Modern Rahmatul Asri Enrekang - Jumarni, Jumarni; Talib, Ahmad; Korompot, Chairil Anwar (State University of Makassar, 2024)
This research aims to explore the students’ self-confidence in speaking English through speech training, and to know the impacts of English speech training on students’ self-confidence. The method used in this research is a qualitative descriptive method, with interview and observation as data instruments. The subjects of this research were female students in class IX MTSS at Pondok Pesantren Modern Rahmatul Asri Enrekang, with the 10 female students as the respondents in class IX MTSS Rahmatul Asri. In this research, the researcher analyzed data by collecting, reducing, presenting data and drawing conclusions. Based on the research results, it was found that students had a good self-confidence in speaking English through English speech training, and English speech training has good impacts on students’ self-confidence development, as evidenced by the results of interview and direct observation. It can be concluded that students can train and increase their confidence in English through English speech training. Keywords: Self-confidence, Speaking, English Speech.